Pengembangan Pemasaran Produk Halal Dalam Peningkatan Pendapatan Masyarakat Kelurahan Jati Makmur Kecamatan Binjai Utara - Dina Zulfa Ofera; Riyan Pradesyah (University of Muhammadiyah Sumatera Utara, 2019)
The development of sharia principles in Indonesia continues to experience a significant increase. This can be seen from the increase in Islamic financial institutions, which use sharia principles. The development of financial institutions, is a major initiator in the emergence of existing Islamic products in Indonesia, then other emerging Islamic products have emerged, such as halal tourism; sharia hotels, halal restaurants, halal medicines and more. In the incessant development of Islamic financial institutions in the midst of society, halal products arise as part of increasing people's income. However, there is still a lack of public knowledge about halal products in circulation, even the people do not know about how to market halal products using the sharia marketing system. This of course is something that must be intensified to be socialized, so that Islamic products can experience development, and also of course can help the community in improving the economy. So for that, socialization in the sharia marketing system is carried out in every village, by describing the Islamic marketing system and profit taking. The existence of this, it is expected that the community can increase their opinion, and know about the sharia marketing system for halal products to be carried out.